Comparison of IL-17 and FOXP3+ Levels in Maternal and Children Leprosy Patients in Endemic and Nonendemic Areas. (25th February 2021) - Prakoeswa, Flora Ramona Sigit; Maharani, Faradiba; Fitriah, Munawaroh; Nugraha, Jusak; Soebono, Hardyanto; Prasetyo, Budi; Martini, Santi; Husada, Dominicus; Notobroto, Hari Basuki; Listiawan, Muhammad Yulianto; Endaryanto, Anang; Prakoeswa, Cita Rosita Sigit
Abstract : Leprosy, a chronic infection caused by M. leprae, has a complex transmission problem that makes eradication programs difficult. New cases and ongoing transmission of leprosy in endemic areas make individuals living in endemic environments vulnerable to leprosy. This can be caused by the dysregulation of immune system in individuals living in leprosy-endemic areas. Although the number of male leprosy patients is higher, female leprosy patients have more impact on the family health status due to close contact with family members, roles in the household, and parenting. This could cause the increased number of children leprosy patients. We investigated the dysregulation of immune system by comparing IL-17 and FOXP3+ levels occurring in maternal and child leprosy patients in endemic and nonendemic areas. The results of the study found a statistically significant difference in IL-17 levels between the MB leprosy patient group and the control group (p = 0.048 ), where higher levels of IL-17 are observed in the control group. A significant difference also was found in FOXP3+ levels between the group of healthy children living in endemic and those living in nonendemic areas (p = 0.047 ), where higher FOXP3+ is observed in the healthy children living in endemic areas group.